Symptomatic drop metastases to the spinal canal and cerebellopontine angle from cerebral oligodendroglioma with DICER1 mutation: a case report and literature review - Kai Wang; Haiping Li; Guoqing Zhou; Hongsheng Ji; Yingchao Liu; Shangchen Xu; Tao Song; Bin Liu (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Symptomatic drop metastases from cerebral oligodendroglioma to the spinal axis or cerebellopontine angle (CPA) are exceedingly rare. While DICER1 mutations are linked to tumor invasion and metastasis across multiple cancers, their roles in oligodendroglioma remains undocumented. Case presentation We describe a recurrent oligodendroglioma with CPA and spinal canal metastases, featuring 1p/19q co-deletion, IDH1 R132H, DICER1 D527Y, TERT promoter mutations, and a novel DICER1 D527Y mutation. Conclusion Symptomatic oligodendroglioma metastases to CPA and spinal regions are rare and correlate with poor prognosis. The identified DICER1 mutation may represent a novel mechanism underlying drop metastases in this tumor type.